HUBUNGAN KONSUMSI BUAH DAN SAYUR SERTA KOPI READY TO DRINK TERHADAP KEJADIAN GANGGUAN SIKLUS MENSTRUASI REMAJA PUTRI - Syifa, Zahira Dwi; Stefani, Megah (Journal of Nutrition College, 2024)
ABSTRACTBackground: As many as 75% of adolescents women aged 12-24 years old experience menstrual cycle disorders. Menstrual cycle disorders are disorders experienced by a woman during the menstrual period which usually occurs due to irregular cycles, excessive pain, menstruation that becomes longer, and menstrual blood that becomes more.Objective: This study aims to analyze the relationship between fruit and vegetable consumption and ready-to-drink coffee on the incidence of menstrual cycle disorders in young women at SMKN 38 Jakarta.Methods: This research method was conducted on 66 adolescent girls who experienced menstrual cycle disorders, consumed vegetables and fruits and ready-to-drink coffee. This study used a cross sectional design with proportional random sampling of subjects. Data analysis using Chi-Square.Results: The results showed that there was a significant relationship between fruit consumption and the menstrual cycle and duration of abdominal pain or cramps of 0.002 and 0.007, consumption of vegetables and menstrual cycle and duration of abdominal pain or cramps of 0.014 and 0.050 and consumption of ready-to-drink coffee with menstrual cycles and duration of pain or abdominal cramps of 0.034 and 0.050 with a p-value <0.05. However, there was no significant relationship between fruit and vegetable consumption and menstrual duration of 0.138 and 1.000 and ready-to-drink coffee with menstrual duration of 0.066 with a p-value > 0.05.Conclusion: In conclusion, the less often someone consume fruits and vegetables and the more frequently you consume ready-to-drink coffee, the more likely you are to experience menstrual cycle disorders and complaints of abdominal pain or cramps during menstruation. It is possible that female students need to pay attention to a balanced and varied diet and limit the consumption of ready-to-drink coffee so that there are no menstrual cycle disturbances and complaints of abdominal pain or cramps during menstruation.Keywords: coffee; fruit; vegetable; menstrual cycle; young women ABSTRAKLatar belakang: Sebanyak 75% remaja putri berusia 12-24 tahun mengalami gangguan siklus menstruasi. Gangguan siklus menstruasi merupakan gangguan yang dialami seorang wanita selama masa periode menstruasi yang biasanya terjadi karena siklus tidak teratur, nyeri yang berlebihan, menstruasi yang waktunya menjadi lebih lama, serta darah menstruasi yang menjadi lebih banyak. Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan konsumsi buah dan sayur serta kopi ready to drink terhadap kejadian gangguan siklus menstruasi remaja putri di SMKN 38 Jakarta.Metode: Metode penelitian ini dilakukan kepada 66 remaja putri yang mengalami gangguan siklus menstruasi, mengkonsumsi sayur dan buah serta kopi ready to drink. Penelitian ini menggunakan desain cross sectional dengan penentuan subjek secara proportional random sampling. Analisis data menggunakan Uji Chi-SquareHasil: Hubungan yang signifikan antara konsumsi buah dengan siklus menstruasi dan lama nyeri atau kram perut sebesar 0,002 dan 0,007 konsumsi sayur dengan siklus menstruasi dan lama nyeri atau kram perut sebesar 0,014 dan 0,050 dan konsumsi kopi ready to drink dengan siklus menstruasi dan lama nyeri atau kram perut sebesar 0,034 dan 0,050 dengan nilai p-value < 0,05. Namun, tidak ada hubungan yang signifikan antara konsumsi buah dan sayur dengan lama menstruasi sebesar 0,138 dan 1,000 serta kopi ready to drink dengan lama menstruasi sebesar 0,066 dengan nilai p-value  > 0,05.Simpulan: Semakin jarang konsumsi buah dan sayur serta semakin rutin konsumsi kopi ready to drink semakin mempunyai peluang terjadinya gangguan siklus menstruasi dan keluhan nyeri atau kram perut saat menstruasi. Kata kunci: kopi; buah; sayur; siklus menstruasi; remaja putri